2017
DOI: 10.2147/ott.s110468
|View full text |Cite
|
Sign up to set email alerts
|

miR-182 promotes tumor growth and increases chemoresistance of human anaplastic thyroid cancer by targeting tripartite motif 8

Abstract: Chemotherapy is one of the most effective forms of cancer treatment and has been used in the treatment of various malignant tumors. We have gained significant insight into the mechanisms of chemoresistance but the details of the molecular mechanisms remain unclear. In the present study, we found that tripartite motif 8 (TRIM8) expression was downregulated in anaplastic thyroid cancer (ATC) tissues and cell lines. This downregulation of TRIM8 was significantly correlated with the upregulation of miR-182 in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
(44 reference statements)
2
27
0
Order By: Relevance
“…Drug resistance is identified as a major obstacle in tumor chemotherapy, and miRNAs have been reported to serve critical roles in this process (17)(18)(19)(20)(21)(22)(23). To date, several studies have identified that miR-149 exerts a critical function in numerous types of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance is identified as a major obstacle in tumor chemotherapy, and miRNAs have been reported to serve critical roles in this process (17)(18)(19)(20)(21)(22)(23). To date, several studies have identified that miR-149 exerts a critical function in numerous types of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have profiled differentially expressed miRNAs in lung cancer, among which miR‐182 was found to be upregulated more than six‐fold . miR‐182 was also demonstrated to contribute to chemoresistance to cisplatin in hepatocellular carcinoma, anaplastic thyroid cancer and colorectal cancer . In the present study, we study the possible role of miR‐182 in radioresistance in NSCLC, and our data show that miR‐182 could be a target for radiosensitization.…”
Section: Introductionmentioning
confidence: 53%
“…8 miR-182 was also demonstrated to contribute to chemoresistance to cisplatin in hepatocellular carcinoma, anaplastic thyroid cancer and colorectal cancer. [9][10][11] In the present study, we study the possible role of miR-182 in radioresistance in NSCLC, and our data show that miR-182 could be a target for radiosensitization.…”
mentioning
confidence: 70%
See 2 more Smart Citations